Current concepts in the treatment of proximal humerus nonunions: a review - Lyubomir Rusimov (Journal of the Bulgarian Orthopaedics and Trauma Association)
Objective:  To review contemporary concepts regarding the etiology, classifications, and treatment of nonunion following proximal humerus fractures (PHFs). Materials and Methods: For the arrangement of this narrative non-systematic review, an exploratory search in the MEDLINE (via PubMed) database using the keywords “proximal humerus” and“nonunion” for a period covering the last ten years was conducted. The search was performed in November,2024 to include the most recent data available in the literature.Conclusions: Proximal humerus nonunion (PHN) is a relatively rare complication following PHFs. The risk of its occurrence is higher in PHFs with medial cortex insufficiency and fractures initially displaced into varus. Poor reduction and lack of fixation stability due to the surgical technique, along with patient-related factors such as smoking, further increase the risk of developing PHN. Researches on the treatment methods involving open reduction and internal fixation (ORIF) for PHN are heterogeneous, with a limited number of studies and  small number of patients, and no method has been established as the gold standard. Regardless of the ORIF method, augmentation with autograft or allograft appears to be mandatory. Compared to ORIF, prosthetic treatment for PHN yields poorer functional outcomes and higher rates of complications and reoperations, regardless of prosthesis type .